Tariff negotiations and renegotiations under the GATT and the WTO : procedures and practices - Hoda, Anwarul, 1938-; World Trade Organization (Cambridge, United Kingdom : Cambridge University Press, 2018)
Over the past seven decades, since the General Agreement on Tariffs and Trade (GATT) was established in 1947, there has been a phenomenal increase in international trade in goods, largely due to sustained efforts by the world's main trading nations to reduce and eliminate tariff barriers in a multilaterally orchestrated manner. This publication reviews how the procedures and practices relating to tariff negotiations and renegotiations have evolved over this time. In particular, this new edition recounts how negotiations to expand the duty-free coverage of the Information Technology Agreement were concluded and provides an account of tariff renegotiations regarding successive enlargements of the European Union. It also covers tariff negotiations for the accession of a number of new members to the WTO, such as China and Russia. This book will be of particular interest to negotiators, members of government, trade ministries, economists and academics specialized in trade policy.
Legal framework for tariff negotiations and renegotiations under GATT 1994 -- Tariff conferences and rounds of multilateral trade negotiations -- Bilateral and plurilateral negotiations -- Practice and procedures in renegotiations -- Schedules of tariff concessions : rectification, modification and consolidation -- Appendix A. Key provisions in the Havana Charter and GATT 1994 and related decision and understandings -- Appendix B. Decisions and declarations commencing rounds of multilateral trade negotiations -- Appendix C. Protocols embodying the results of multilateral trade negotiations -- Appendix D. Decisions on procedures on renegotiations, rectifications, modifications and related subjects.
Online resource; title from digital title page (viewed on January 22, 2019).
Includes bibliographical references (pages 395) and index.
eBooks on EBSCOhost
Keywords: World Trade Organization -- Rules and practice; General Agreement on Tariffs and Trade (Organization) -- Rules and practice; General Agreement on Tariffs and Trade (Organization); World Trade Organization; Tariff -- Law and legislation; Negotiation; Negotiating; Négociations.; BUSINESS & ECONOMICS -- Exports & Imports; BUSINESS & ECONOMICS -- International -- General; BUSINESS & ECONOMICS -- International -- Marketing; POLITICAL SCIENCE -- International Relations -- Trade & Tariffs; Negotiation; Foreign trade regulation; Parliamentary practice; Tariff -- Law and legislation; Rules